Proud boys and the white ethnostate : how the alt-right is warping the American imagination - Stern, Alexandra Minna, 1966- (Beacon Press, 2019)
"From a loose movement that lurked in the shadows in the early 2000s, the alt-right has achieved a level of visibility that has allowed it to expand significantly through America's cultural, political, and digital landscapes. Yet it is also mercurial and shape-shifting, encompassing a spectrum of ideas and believers that resonate with white supremacy, right-wing nationalism, and anti-feminism. The alt-right offers a big and porous tent to those who subscribe to varying forms of race- and gender-based exclusion and endorse white identity politics. To understand the contemporary moment, historian Alexandra Minna Stern knew she needed to get under- to excavate- the alt-right memes and tropes that had erupted online. In Proud Boys and the White Ethnostate, she does just that, applying the tools of the scholar to explore the alt-rights central texts, narratives, constructs, and insider language"--